Isolamento e identificação de Cryptococcus spp. a partir de amostras ambientais do entorno de hospitais da cidade de Belo Horizonte - Amanda Cristina Araújo (2022)
Cryptococcus spp. are encapsulated, cosmopolitan, globally distributed yeasts frequently associated with bird excrements. The main species of clinical importance are the so- called Cryptococcus gattii/neoformans complex, however, other species are also reported to cause disease in patients with or without immunological impairment, the first group being most commonly affected. Some of these species are currently reclassified into genera such as Papiliotrema sp., Kwoniella sp. and Naganishia sp. Ecoepidemiological studies are important for the mapping and prevention of risks associated with diseases since they contemplate not only the microorganism. Thus, the present study aimed to verify the presence of these yeasts and their relationship with the environment and the potential risk associated with them. The samples were collected from five hospitals in the city of Belo Horizonte, with a considerable flow of immunosuppressed patients. The collected material was submitted to processing and isolation of yeasts, hich were identified by molecular biology and evaluated for thermotolerance, melanization and production of enzymes such as proteinase, phospholipase, urease and catalase. Among the isolates, although no representatives of the C. gattii/neoformans complex were found, there was a positive percentage of 17,54% (50/285) for other species that can also be considered of increasing clinical relevance. In the Belo Horizonte hospitals surroundings, yeasts of the genera Papiliotrema (66% - 33/50), Naganishia (18% - 9/50), Kwoniella (14% - 7/50) and Hannaella (2% - 1/50) were found, being divided among the species Papiliotrema laurentii (34,00% - 17/50), Papiliotrema terrestris (20,00% - 10/50), Papiliotrema flavescens (4,00% - 2/50), Papiliotrema rajasthanensis (2,00% - 1/50), Naganishia albida (8,00% - 4/50), Naganishia diffluens (4,00% - 7/50), Naganishia cerealis (2,00% - 1/50), Kwoniella heveanensis (14% - 7/50) and Hannaella luteola (2,00% - 1/50). P. laurentii and K. heveanensis was present in all hospitals and, considering the virulence tests, P. laurentii was the only species with positive representatives in 7 of the 9 tests applied (20% - 10/50). These results show us that, although less common in case reports and scientific research, species not belonging to the C. gatti/neoformans complex and currently reclassified may present virulence factors and favorable dispersal conditions for the microorganism in a possible host infection.